29-3c=9(7c+2)

Simple and best practice solution for 29-3c=9(7c+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 29-3c=9(7c+2) equation:


Simplifying
29 + -3c = 9(7c + 2)

Reorder the terms:
29 + -3c = 9(2 + 7c)
29 + -3c = (2 * 9 + 7c * 9)
29 + -3c = (18 + 63c)

Solving
29 + -3c = 18 + 63c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-63c' to each side of the equation.
29 + -3c + -63c = 18 + 63c + -63c

Combine like terms: -3c + -63c = -66c
29 + -66c = 18 + 63c + -63c

Combine like terms: 63c + -63c = 0
29 + -66c = 18 + 0
29 + -66c = 18

Add '-29' to each side of the equation.
29 + -29 + -66c = 18 + -29

Combine like terms: 29 + -29 = 0
0 + -66c = 18 + -29
-66c = 18 + -29

Combine like terms: 18 + -29 = -11
-66c = -11

Divide each side by '-66'.
c = 0.1666666667

Simplifying
c = 0.1666666667

See similar equations:

| 6=7y+3 | | 6r-12=3+7r | | -20b=280 | | 345-4532x=12 | | 3y+2-4=6 | | 8x=16x+24 | | 2(6-2y)+4y=12 | | -5(1+6r)=22 | | 60*60*0+1= | | 22+8p=5p+4(p+4) | | 130.00=.80x+18 | | -22+7c=-5(4c+6) | | 2x(2)+17x+35=0 | | 3x(9)=24 | | x/281=40/360 | | 2x+13-7+6x= | | -16=-3(6k+9) | | 23=2+8(r+5) | | -20=-9d-2d | | 4.2+7=2.8 | | 3p^2+24p=-105 | | 6x^2-13b=0 | | 3-3*6+3=-13 | | -6+8(1-2x)=27 | | 9y+8+7=-26 | | (x+5)2=(2x)2 | | -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 |

Equations solver categories